The Effect of Management Information Systems on Managerial Performance in PT. Sucofindo (Persero) - Ramadhani, Ayulita; Syahputra, Akbar; Hermawan, Dedi (Budapest International Research and Critics University, 2022)
This study aims to determine the effect of Management Information Systems on managerial performance at PT. SUCOFINDO (Persero) Medan Branch Office. The population in this study were employees of the company totaling 33 people. Hypothesis testing with the help of SPSS program IBM Statistics version 25. Based on the results of this study indicate that the independent variable in this case is the management information system has a positive and significant influence on the dependent variable in this case is the managerial performance with significance value is 0.009 < 0.05. Then the management information system affects the managerial performance at PT. SUCOFINDO (Persero) Medan Branch Office.